Exploring the Effectiveness of Think-Pair-Share Approach in Teaching Comparative Degree to Junior High School Grade 8 Students - Viriana (P-SEMART JOURNAL, 2022)
This study aimed to explore the effectiveness of the Think-Pair-Share (TPS) approach in teaching comparative degree to 42 Junior High School Grade 8 students in a single class, class 8-I. The TPS approach is an active learning strategy that involves students in a collaborative process of sharing and discussing ideas. The research design used in this study was a quasi-experimental design with a pretest-posttest control group design. The participants of this study were divided into an experimental group and a control group. The experimental group was taught using the TPS approach, while the control group was taught using traditional lecture-based teaching. The results showed that there was a significant difference in the post-test scores between the experimental group and the control group, with the experimental group performing better. The findings suggest that the TPS approach can be an effective teaching strategy for teaching comparative degree to Junior High School Grade 8 students in class 8-I. This study explores the effectiveness of the TPS approach in teaching comparative degree to Junior High School Grade 8 students in class 8-I. The results showed that the TPS approach is an effective teaching strategy, enhancing student understanding and academic performance. These findings have implications for promoting active learning and innovative teaching methods.